Performance assessment of a thermoelectric generator applied to exhaust waste heat recovery - Demir, Murat Emre; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In this study, we propose a novel system for recovering waste heat of the automobile by means of a system based thermoelectric generator. The waste heat recovery (WHR) system is designed to be located after the exhaust manifold of the automobile for recovering and using the recovered heat, and it consists of a shell and tube heat exchanger whose pipes are covered with thermoelectric materials. The exhaust gas of the automobile supplies the heat for the thermoelectric generator (TEG), and the incoming air from the front grill maintains the temperature difference for the TEG. Three different Perovskite-type oxide combined thermoelectric materials (CaMn0.98Nb0.02O3, La1.98Sr0.02CuO4 and GdCo0.95Ni0.05O3) are selected, considered and analyzed numerically. The variations of material properties, efficiency and power generated with respect to temperature and position are presented. The overall heat to electricity conversion efficiency of the TEG system is introduced by dimensionless quantities. The overall energy and exergy efficiencies of the heat recovery system are correlated and presented. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Heat transfer; Heat recovery; Thermoelectric generator; Energy management; Exergy; Efficiency; POWER POINT TRACKING; AUTOMOTIVE APPLICATION; SYSTEM; MODEL; EXCHANGER; ENGINE; GAS; Thermodynamics; Energy & Fuels; Engineering; Mechanics